1991
DOI: 10.1136/jmg.28.8.505
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical studies show truncated dystrophins in the myotubes of three fetuses at risk for Duchenne muscular dystrophy.

Abstract: We have performed immunohistochemical studies on muscle tissue of three 12 week old fetuses at risk for DMD, using antisera directed against regions located NH2-proximally and centrally in the rod shaped spectrin-like domain and against the COOH-terminus of dystrophin. All three fetuses had a family history ofDMD. Truncateddystrophins were identified in all three cases by a positive reaction with the NH2-proximal antibody, different reactions with the central antibody, and a negative reaction with the COOH-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…At early fetal stages dystrophin was detected in atrial cardiomyocytes and in the specialized cardiomyocytes that constitute the conduction system of the ventricle. In the heart of a 12-week-old DMD fetus (Ginjaar et al, 1991) dystrophin could not be detected.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…At early fetal stages dystrophin was detected in atrial cardiomyocytes and in the specialized cardiomyocytes that constitute the conduction system of the ventricle. In the heart of a 12-week-old DMD fetus (Ginjaar et al, 1991) dystrophin could not be detected.…”
Section: Introductionmentioning
confidence: 81%
“…Interestingly, at this stage it is now predominantly found in the sarcolemma of the myocytes of the His-bundle ( Fig. 6 0 . In the heart of a fetus of 12 weeks of development found to be affected with DMD (family 2, Ginjaar et al, 1991), a-MHC is observed in the bundle branches (Fig. 7A), whereas dystrophin is absent in these cardiomyocytes (Fig.…”
Section: Arrows Indicate Myofibrillsmentioning
confidence: 99%
“…The symptoms worsened over time, suggesting that the 70–80‐kDa dystrophin was unable to restore sarcolemmal stability. In a separate study, immunohistochemical assays revealed expression of truncated dystrophin in myotubes isolated from three 12‐week‐old aborted fetuses at risk for DMD, suggesting that mutant dystrophin is synthesized in human DMD patients . Recently, the truncated form of dystrophin was detected within the ER/Golgi compartments of mdx mice , suggesting that the 115‐kDa dystrophin may be retained in the ER/Golgi compartments.…”
Section: Protein Aggregation and Amelioration In Muscular Dystrophiesmentioning
confidence: 94%
“…However, dystrophin mRNA levels vary widely, depending on the causative mutation in human DMD and Becker muscular dystrophy patients . It was previously thought that the 115 kDa dystrophin protein is rapidly degraded after synthesis in mdx muscle, but studies suggest that truncated dystrophin may be expressed at the sarcolemma or retained in the ER/Golgi .…”
Section: Protein Aggregation and Amelioration In Muscular Dystrophiesmentioning
confidence: 99%